Grandmother and health care professional breastfeeding perspectives provide opportunities for health promotion in an American Indian community - Houghtaling, Bailey (Soc Sci Med, 2018)
RATIONALE: While breastfeeding is well recognized as beneficial, rates of breastfeeding among American Indian women are below average and contribute to health inequities. Culturally specific approaches to breastfeeding research are called for to inform appropriate interventions in American Indian communities. Specifically, a grandmother's role in breastfeeding promotion is of great import particularly in American Indian (AI) groups, although is an understudied topic to date. OBJECTIVE: This research seeks to fill a prominent literature gap by utilizing a grounded theory and community-based research approach to inform breastfeeding practices from the voices of grandmothers and health care professionals in a rural AI community in the United States. METHODS: A community-based approach guided the research process. Convenience and snowball sampling was used to recruit for semi-structured and follow up member checking interviews with AI grandmothers (n = 27) and health care professionals (n = 7). Qualitative data were transcribed, characterized into meaning units, and coded by a review panel. Data were reconciled for discrepancies among reviewers, organized thematically, and used to generate community-specific breastfeeding constructs. RESULTS: Three major themes emerged, each with relevant subthemes: (1) importance of breastfeeding; (2) attachment, bonding, and passing on knowledge; and (3) overburdened health care system. Multiple subthemes represent stressors and impact breastfeeding knowledge, translation, and practice within this community including formula beliefs, historical traumas, societal pressures, mistrust, and substance abuse. CONCLUSIONS: Interventions designed to raise breastfeeding rates in the study site community would ideally be grounded in tribal resources and involve a collaborative approach that engages the greater community, grandmothers, health care professionals, and scientific partners with varying skills. More research is needed to determine stressors and any potential impact on infant feeding practices among other AI groups. Application of the research approach presented here to other AI communities may be beneficial for understanding opportunities and challenges to breastfeeding practices.